Peran keluarga sebagai tempat pertama sosialisasi budi pekerti Jawa bagi anak dalam mengantisipasi degradasi nilai-nilai moral - Amirotun Sholikhah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2020)
The family is the smallest unit in society that is formed due to the marriage ties between men and women. The development of children in the family is influenced by the condition of the family situation and the experiences of the parents. The family is a place for the socialization of values ​​or life roles in society carried out by its members. The family goal is the rules and values ​​are known and understood by children so that they can eventually become independent individuals, behave and act according to the rules and values ​​that apply. Javanese character is a value that developed in Javanese society sourced from local religious and cultural norms, can be socialized within the family, among others, through the example given by parents to their children from an early age so as to be equipped in social life as an independent person and not deviate from the prevailing norm.